2020
DOI: 10.1021/acssynbio.9b00498
|View full text |Cite
|
Sign up to set email alerts
|

Guide RNA Engineering Enables Dual Purpose CRISPR-Cpf1 for Simultaneous Gene Editing and Gene Regulation in Yarrowia lipolytica

Abstract: Yarrowia lipolytica has fast become a biotechnologically significant yeast for its ability to accumulate lipids to high levels. While there exists a suite of synthetic biology tools for genetic engineering in this yeast, there is a need for multipurposed tools for rapid strain generation. Here, we describe a dual purpose CRISPR-Cpf1 system that is capable of simultaneous gene disruption and gene regulation. Truncating guide RNA spacer length to 16 nt inhibited nuclease activity but not binding to the target lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Truncating sgRNA could inhibit the nuclease activity of Cas protein, but not influence the targeting effect. On this basis, a Cpf1-VPR fusion with truncated sgRNA (16 bp) increased hrGFP expression by 10-fold in Y. lipolytica ( Ramesh et al, 2020 ).…”
Section: Advanced Crispr/cas Technology In Non-conventional Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Truncating sgRNA could inhibit the nuclease activity of Cas protein, but not influence the targeting effect. On this basis, a Cpf1-VPR fusion with truncated sgRNA (16 bp) increased hrGFP expression by 10-fold in Y. lipolytica ( Ramesh et al, 2020 ).…”
Section: Advanced Crispr/cas Technology In Non-conventional Yeastsmentioning
confidence: 99%
“…In C. glabrata , the choice of the promoter may influence the type of mutation, a single base pair or larger insertions were observed when different promoters were used to express Cas9 ( Enkler et al, 2016 ) . In Y. lipolytica , different promoters were screened for nCas9-pmCDA1-UGI expression, and the highest efficiency was achieved by TFFin promoter ( Ramesh et al, 2020 ). These findings show that an appropriate level of Cas9 expression is beneficial to the strain’s resilience and genome editing efficiency.…”
Section: Optimization Of Crispr/cas System In Non-conventional Yeastmentioning
confidence: 99%
“…The gene integration efficiency of up to 55% has been achieved using a homology‐independent targeted genome integration tool mediated by CRISPR/Cas9 which does not require the construction of homologous templates (Cui et al, 2021). More recently, a dual‐purpose CRISPR‐Cpf1 system has been suggested that is capable of simultaneous gene disruption and gene regulation in Y. lipolytica (Ramesh et al, 2020). Furthermore, a suite of genetic tools (EasyCloneYALI) has been generated that facilitates transformation protocols by providing a series of pre‐designed plasmids and oligos (Holkenbrink et al, 2018).…”
Section: Wet‐lab Tools To Facilitate Systems Analysismentioning
confidence: 99%
“…To create the LbCas12a sgRNA expression plasmid (pLbCas12ayl), we first added a second direct repeat sequence at the 5' of the polyT terminator in pCpf1_yl (see ref. 41 ). This was done to ensure that library sgRNAs could end in one or more thymine residues without being construed as part of the terminator.…”
Section: Plasmid Constructionmentioning
confidence: 99%